Strategi Digital Public Relations PT. Toffee International dalam Membangun Brand Awareness melalui Event SEOCON - Lee, Chris; Setyanto, Yugih (Kiwari, 2024)
Rapid technological advances require humans to be able to adapt. This can be seen from the emergence of the internet which has influenced human activities, including in the field of work. One of the activities affected by the emergence of the internet is public relations activities. Therefore, it is very important to carry out research or in-depth studies to see the impact of adopting digital technology in the world of public relations, looking further at what public relations authorities are preparing today both in organizations and in commercial businesses. This research was conducted to see how to elevate the digital public relations strategy carried out by PT. Toffee International or known as ToffeeDev in building company brand awareness through the SEOCON event. This research uses a qualitative approach with a case study method at PT. Toffee International as organizer of the SEOCON event. The results of this research found that several digital public relations strategies that had been carried out by PT. Toffee International provides company websites and event websites, carries out advertising on search engines such as Google, publishes content related to digital marketing on social media, and organizes events such as webinars, seminars, workshops and conferences. SEOCON is an international conference related to digital marketing held by ToffeeDev every year starting from 2019. Kemajuan teknologi yang pesat, mengharuskan manusia untuk dapat beradaptasi. Hal tersebut dapat dilihat dari kemunculan internet yang memengaruhi kegiatan manusia termasuk di bidang pekerjaan. Salah satu kegiatan yang terdampak akibat kemunculan internet adalah kegiatan public relations. Oleh karena itu sangat penting untuk dilakukan penelitian atau telaah mendalam untuk melihat dampak pengadopsian teknologi digital dalam dunia public relation, melihat lebih jauh apa yang hari disiapkan oleh pemegang otoritas public relation baik dalam organisasi maupun dalam bisnis komersial. Penelitian ini dilakukan untuk melihat mengangkat strategi digital public relations yang dilakukan PT. Toffee International atau dikenal ToffeeDev dalam membangun brand awareness perusahaan melalui event SEOCON. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus pada PT. Toffee International sebagai penyelenggara event SEOCON. Hasil pada penelitian ini ditemukan bahwa beberapa strategi digital public relations yang telah dilakukan PT. Toffee International adalah menyediakan website perusahaan dan website event, melakukan advertising/iklan pada mesin pencari seperti Google, publikasi konten terkait digital marketing di media sosial, dan menyelenggarakan event-event seperti webinar, seminar, workshop, dan konferensi. SEOCON merupakan konferensi internasional terkait digital marketing yang diadakan oleh ToffeeDev setiap tahun mulai dari tahun 2019.